Comparison of Risk Factors for Hypertrophic Osteodystrophy, Craniomandibular Osteopathy and Canine Distemper Virus Infection - Munjar, T. A.; Austin, Connie C.; Breur, G. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
An analysis of hypertrophic osteodystrophy (HOD), craniomandibular osteopathy (CMO) and canine distemper virus (CDV) infection was undertaken. Risk factors (age, breed, sex, neuter status, weight, geographical and seasonal distribution) of the three diseases were determined and compared. Patient records were searched using the Veterinary Medical Database (VMDB) during the period of 1980 through 1989. This search identified 131 cases of HOD, 68 cases of CMO and 1,757 of CDV infection. Dogs less than six months of age were identified to be at greatest risk for HOD, CMO and CDV. The Great Dane, Cairn Terrier and the Greyhound were identified to be at highest risk for HOD, CMO and CDV infection, respectively. Males puppies were twice as likely to develop HOD. We concluded, from the risk factors analyzed, that risk factors for HOD, CMO or CDV infection were not similar.Patient information was obtained from clinical cases of 16 veterinary teaching hospitals to examine a possible relationship between Hypertrophic Osteodystrophy (HOD), Craniomandibular Osteopathy (CMO), and Canine Distemper Virus (CDV) infections. Risk factors for each disease were determined. Subjective comparison of risk factors for HOD and CMO did not support the notion of a relationship between HOD and CMO. In addition, no evidence for a possible relationship between CDV and HOD or CMO was found.
Keywords: Hypertrophic osteodystrophy; craniomandibular osteopathy; canine distemper virus